Dukungan Keluarga Dengan Tingkat Kecemasan Pada Mahasiswa Yang Tinggal Dengan Keluarga Berbeda Dengan Mahasiswa Yang Tinggal Di Kost Dalam Menyusun Skripsi: Family Support with Anxiety Levels in Students Who Live with Different Families from Students Who Live in Boarding Houses in Compiling Thesis - Gea, One Jul (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Students are individuals who are studying in higher education, the desire of students to receive higher education is motivated by their aspirations, including mastering science and technology, skills, and high status in society. However, achieving these goals is not an easy thing, there are many obstacles and challenges that they must face both inside and outside the campus. Methods: The method used in this research is cross-sectional on 120 respondents with Spearman and Wilcoxon Rank analysis. This research was conducted at the Advanced Indonesian School of Health Sciences (STIKIM), measuring family support using the Family Support Scale questionnaire, and measuring anxiety levels using the HARS (Hamilton Rating Scale of Anxiety) questionnaire. Results: The results of this study found that there was a significant difference in family support with anxiety levels in students who stay with family and stay in a boarding house in making essays (p-value= 0,000). Discussion: There is a significant difference between family support and the level of anxiety in students who live with their families and live in boarding houses in compiling their thesis at STIKIM in 2018. Family support is one alternative in reducing the level of student anxiety in writing a thesis.